2013
DOI: 10.1016/j.bbamcr.2013.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Symplekin, a polyadenylation factor, prevents MOZ and MLL activity on HOXA9 in hematopoietic cells

Abstract: MOZ and MLL encoding a histone acetyltransferase and a histone methyltransferase, respectively, are targets for recurrent chromosomal translocations found in acute myeloblastic or lymphoblastic leukemia. We have previously shown that MOZ and MLL cooperate to activate HOXA9 gene expression in hematopoietic stem/progenitors cells. To dissect the mechanism of action of this complex, we decided to identify new proteins interacting with MOZ. We found that the scaffold protein Symplekin that supports the assembly of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…KAT6A (lysine acetyltransferase 6 A), formerly called MOZ or MYST3, is involved in normal hematopoietic stem/progenitor cells functions. We have previously demonstrated that KAT6A is a partner of KMT2A (MLL) and Symplekin in hematopoietic stem/progenitor cells 12 , 13 . Compared to other MYST family members, KAT6A and KAT6B (or MORF) harbor unique structural functional domains 14 .…”
Section: Resultsmentioning
confidence: 99%
“…KAT6A (lysine acetyltransferase 6 A), formerly called MOZ or MYST3, is involved in normal hematopoietic stem/progenitor cells functions. We have previously demonstrated that KAT6A is a partner of KMT2A (MLL) and Symplekin in hematopoietic stem/progenitor cells 12 , 13 . Compared to other MYST family members, KAT6A and KAT6B (or MORF) harbor unique structural functional domains 14 .…”
Section: Resultsmentioning
confidence: 99%
“…Symplekin (Sympk) is a ubiquitously expressed protein that assembles in various protein complexes and displays dynamic functions in different biological process including cytoplasmic RNA polyadenylation , epithelial tight‐junction assembly , transcriptional modulation , kidney and intestinal cell differentiation , hematopoietic stem/progenitor cells , tumorigenesis , colon cancer cell growth and de‐differentiation , and mitosis in lung cancer cells . However, the role of Sympk in ESCs has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%